Non-Native English Lecturers' Motivational Practices in a Tertiary Educational Environment - Nur, Sahril; Hardini, Tri Indri; Patak, Andi Anto (Indonesian Journal of Applied Linguistics, 2021)
To fill in the gap on how tertiary educational environment’s non-native English lecturers in Indonesia use all motivational activities, this qualitative case study examined how they think about motivational strategies in the classroom, how they put the knowledge into effect, and how EFL students think about their lecturers' motivational strategies. This study focused on a single embedded design in which participants from a single organization were divided into two major clusters. Interviews with five non-native English lecturers and thirteen English Literature students, observation, and field notes were utilised. The participants believed that there are two types of motivation: natural and nurtured, with nurturing motivation receiving more attention. The instructor element is central to motivation, according to participants in both clusters. Both participants stressed the importance of getting a figure to obey. This understanding was positively reflected in practices where lecturers developed, produced, and sustained motivational teaching strategies in the classroom, demonstrating dominance. Sharing non-native English lecturers' success stories, contextualizing, and encouraging were among the study's specific activities. Motivation is essential for learning, but the type and techniques used can differ depending on the situation. These results indicate that a proper and replicable Motivational Teaching Practices (MTP) paradigm necessitated national or regional adaptations due to contextual factors. However, MTP components relevant to English Literature students were ignored by lecturers. Realising MTP’s importance may lead to successfully achieving learning outcomes in higher educational settings.